Ethnobotanical study of medicinal plants by population of Valley of Juruena Region, Legal Amazon, Mato Grosso, Brazil. (15th September 2015) - Bieski, Isanete Geraldini Costa; Leonti, Marco; Arnason, John Thor; Ferrier, Jonathan; Rapinski, Michel; Violante, Ivana Maria Povoa; Balogun, Sikiru Olaitan; Pereira, João Filipe Costa Alves; Figueiredo, Rita de Cassia Feguri; Lopes, Célia Regina Araújo Soares; da Silva, Dennis Rodrigues; Pacini, Aloir; et al.
Abstract: Ethnopharmacological importance: The use of medicinal plants for treatment, cure and prevention of diseases has been described by many people since time immemorial. Because of this use, commercial and scientific interests have emerged, making it necessary to realize ethnobotanical surveys of medicinal plants species, which is important for subsequent chemical and pharmacological bioprospections. Aim of the study: This study aimed at surveying, identifying, cataloging and documenting the medicinal plants species used in the Valley of Juruena, Northwestern Mato Grosso, Legal Amazon Brazil for the treatment of various human diseases, as well as assessed the species of interest for bioprospecting potential. Materials and methods: Informants were interviewed using semi-structured form to capture information on socio-demographic and ethnopharmacological data of medicinal plants such as vernacular name, uses, geographic origin, habit, form of preparation and part used. Results were analyzed using descriptive and quantitative means: indices of use-report (Ur) and informant consensus factor (ICF), for the selection of plant species with therapeutic potential. Results: Three hundred and thirty two (332) plants species belonging to 90 families were reported for medicinal purposes and totaling 3973 use-reports were reported by 365 (92.9%) of the people interviewed. Asteraceae (32.2%), Fabaceae (26.7%) and Lamiaceae (24.4%) families were the most represented, with majority being species native (64.45%) to Brazil. Leaves (64.5%) were the part of the plant most used and infusion (45.7%) was the most utilized form. Gastrointestinal disorders followed by respiratory complaints topped the list of use-reports. The native or naturalized plants with the highest use reports in the order of decreasing absolute frequency per each emic-category are Cymbopogon citratus (DC.) Stapfc (104), Mentha pulegium L. (94), Arrabidaea chica (Humb. & Bonpl.) B. Verl. (97), Alternanthera brasiliana (L.) Kuntze (71), Baccharis crispa Spreng (57), Phyllanthus niruri L. (48), Gossypium barbadense L. (44), Solidago microglossa DC. (40) and Bauhinia forficata L. (20). And the most cited exotics are: Chenopodium ambrosioides L. (151), Aloe vera (L.) Burm. f., (89) and Rosmarinus officinalis L. (72). In some cases, high ICF values were found, which reflects high degree of homogeneity of consensus among informants in this region on medicinal plants. Conclusion: The population of Valle of Juruena makes use of a wide array of medicinal plants distributed in all use categories with predominance of those use in the treatments of gastrointestinal and respiratory ailments. The therapeutic potential of some of the species of medicinal importance extensively utilized by the population of the region have been scientifically validated, and are therefore promising prototype of new drugs. However, there are some of these species whose ethnomedicinal uses are yet to be scientifically verified and thus constitute an unexplored terrain for future biological/pharmacological studies. Graphical abstract: